Dynamic contact response of a finite beam on a tensionless Pasternak foundation under symmetric and asymmetric loading - Coskun, Irfan (TECHNO-PRESS, 2010)
The dynamic response of a finite Bernoulli-Euler beam resting on a tensionless Pasternak foundation and subjected to a concentrated harmonic load is investigated in this study. This load may be applied at the center of the beam, or it may be offset from the center. Since the elastic foundation is assumed to be tensionless, the beam may lift off the foundation, resulting in contact and non-contact regions in the system. An analytical/numerical solution is obtained from the governing equations of the contact and non-contact regions to determine the coordinates of the lift-oft points. Although there is no nonlinear term in the equations, the problem appears to be nonlinear since the contact regions are not known in advance. Due to that nonlinearity, the essentials of the problem (the coordinates of the lift-off points) are calculated numerically using the Newton-Raphson technique. The results, which represent the symmetric and asymmetric responses of the beam, are presented graphically in this work. They illustrate the effects of the forcing frequency and the beam length on the extent of the contact regions and displacements.
Keywords: finite beam; Pasternak foundation; lift-off; harmonic load; FREE-VIBRATIONS; ELASTIC-FOUNDATION; NONLINEAR VIBRATIONS; SOIL; SEPARATION; ONSET; Engineering